Active suspension control with consensus strategy for dynamic posture tracking of wheel-legged robotic systems on uneven surfaces. (December 2022) - Liu, Dongchen; Wang, Junzheng; Lei, Tao; Wang, Shoukun
Abstract: This work presents a dynamic posture tracking control strategy for wheel-legged systems on uneven surfaces. Based on the kinematic model of a wheel-legged robotic system, the expected positions for the end-effectors of wheel-legs are calculated according to posture references and sensor feedback. The position control problem for a general wheel-leg is investigated for the active mechanism to imitate a passive suspension and respond to the external contact forces. The position tracking accuracy of the wheel-leg is sacrificed to enhance the compliance performance under rough terrain. Because of the unique contact state with the uneven ground for each wheel-leg, the position responses are different. As a result, the forces from the wheel-legs to the fuselage are inconsistent, which leads to the risk of posture oscillations. Equipping the wheel-legs with an undirected communication network, a consensus scheme for the robotic system is developed with proven global asymptotic stability to improve the posture tracking property. A novel robotic system is established with Stewart-structured wheel-legs, which are connected by a user datagram protocol network. Comparative experimental results are carried out on the physical prototype to validate the effectiveness of the proposed approach. Highlights: An improved kinematic model avoiding geomagnetism disturbances is established for general wheel-legged robotic systems. Considering the contact forces, an active suspension controller is proposed for the single wheel-leg to track the desired position with expected compliance behaviors. Based on an undirected communication topology, a consensus strategy is carried out for multiple ASCs. The CASC fulfills the coordination requirements and active suspension response demands with proved convergency property. The proposed posture control scheme is applied to a wheel-legged physical prototype. The comparative experimental results between the proposed CASC and our previous studies are presented, which highlights the CASC in posture tracking accuracy and wheel-leg coordination performances.